Masseter Muscle Hernia: Rare Case Report of Surgical Management via Preauricular Approach and Mesh - José Ignacio Fonseca-Sada, MD; Yanko Castro-Govea, MD, PhD; Hatan Mortada, MBBS; Edson René Marcos-Ramírez, MD; Alan Amado Méndez-Pérez, MD; Karla Valeria Palomo-Barbosa, MD; Melissa Fernanda Ochoa-Cortez, MD (Plastic and Reconstructive Surgery, Global Open)
Summary:. Masseter muscle hernia (MMH) is an exceptionally rare condition characterized by muscle protrusion through a weakened fascia, with only 4 cases previously reported worldwide. Typically presenting as an asymptomatic tumor at the mandibular angle, MMH becomes more evident during mastication. Diagnosis relies on dynamic imaging, such as ultrasound, whereas treatment remains undefined due to its rarity. We report a novel case of MMH managed surgically with a preauricular approach and mesh reinforcement. A 35-year-old woman presented with a 6-month history of a painful, ovoid tumor (25 × 18 mm) at the right mandibular angle, exacerbated by chewing. Physical examination revealed a semisoft mass that hardened and enlarged with teeth clenching, reducing in size at rest. Dynamic ultrasound confirmed MMH by demonstrating muscle protrusion during contraction. Surgical intervention involved a preauricular approach, dissection of the superficial musculoaponeurotic system, primary closure of a 1 × 1.8 cm fascial defect, and polypropylene mesh reinforcement. The patient recovered well, with no recurrence at 12-week follow-up. This case highlighted MMH as a rare entity, predominantly affecting young women, with pain distinguishing it from prior asymptomatic reports. Dynamic ultrasound proved effective for diagnosis, and surgical repair with mesh reinforcement offered a successful outcome. This approach may serve as a viable option for managing similar cases, expanding the limited treatment repertoire for this uncommon condition.